Favoritism by the governing elite - Zareh Asatryan; Thushyanthan Baskaran; Carlo Birkholz; Patrick Hufschmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
In this paper, we study the extent to which ministers engage in regional favoritism. We are the first to provide a comprehensive analysis of a larger set of the governing elite, not just focusing on the primary leader. We manually collect birthplaces of this governing elite globally. Combining this information with extended nighttime luminosity and novel population data over the period from 1992 to 2016, we utilize a staggered difference-in-differences estimator and find that birthplaces of ministers globally emit on average roughly 9 % more nightlight. This result is predominantly attributable to the African sub-sample. We find no evidence that the measured effect is driven by, or induces, migration to the home regions of ministers. The size of our data set lets us investigate heterogeneities along a number of dimensions: political power, ministerial portfolio, and the institutional setting. – – In dieser Studie untersuchen wir, in welchem Ausmaß Minister regionale Begünstigung betreiben. Wir sind die Ersten, die eine umfassende Analyse eines größeren Datensatzes der regierenden Elite vornehmen, der sich nicht nur auf Staatsoberhäupter bzw. Regierungschefs konzentriert. Dazu sammeln wir Informationen über die Geburtsorte von Ministern weltweit durch qualitative Recherche. Diese Informationen kombinieren wir mit erweiterten Daten zur nächtlichen Beleuchtung und Bevölkerungsdaten für den Zeitraum von 1992 bis 2016. Wir verwenden einen gestaffelten Difference-in-Differences-Schätzer und stellen fest, dass die Geburtsorte von Ministern im Durchschnitt etwa 9% mehr Nachtlicht ausstrahlen. Dieser Effekt wird hauptsächlich von afrikanischen Ländern getrieben. Darüber hinaus finden wir keine Hinweise darauf, dass dieser Effekt durch Migration in die Heimatregionen von Ministern verursacht oder gefördert wird. Die Größe unseres Datensatzes ermöglicht es uns, Heterogenitäten entlang einer Reihe von Dimensionen zu untersuchen: politische Macht, Portfolios und institutionelle Rahmenbedingungen.
Keywords: D72; H72; H77; R11; 330; Favoritism; elite capture; spatiality; luminosity; population; democracy